Therapeutic potential of targeting microRNA‐10b in established intracranial glioblastoma: first steps toward the clinic - Nadiya M Teplyuk; Erik J Uhlmann; Galina Gabriely; Natalia Volfovsky; Yang Wang; Jian Teng; Priya Karmali; Eric Marcusson; Merlene Peter; Athul Mohan; Yevgenya Kraytsberg; Ron Cialic; et al. (EMBO Molecular Medicine)
Abstract MicroRNA‐10b (miR‐10b) is a unique oncogenic miRNA that is highly expressed in all GBM subtypes, while absent in normal neuroglial cells of the brain. miR‐10b inhibition strongly impairs proliferation and survival of cultured glioma cells, including glioma‐initiating stem‐like cells (GSC). Although several miR‐10b targets have been identified previously, the common mechanism conferring the miR‐10b‐sustained viability of GSC is unknown. Here, we demonstrate that in heterogeneous GSC, miR‐10b regulates cell cycle and alternative splicing, often through the non‐canonical targeting via 5′UTRs of its target genes, including MBNL1‐3, SART3, and RSRC1. We have further assessed the inhibition of miR‐10b in intracranial human GSC‐derived xenograft and murine GL261 allograft models in athymic and immunocompetent mice. Three delivery routes for the miR‐10b antisense oligonucleotide inhibitors (ASO), direct intratumoral injections, continuous osmotic delivery, and systemic intravenous injections, have been explored. In all cases, the treatment with miR‐10b ASO led to targets’ derepression, and attenuated growth and progression of established intracranial GBM. No significant systemic toxicity was observed upon ASO administration by local or systemic routes. Our results indicate that miR‐10b is a promising candidate for the development of targeted therapies against all GBM subtypes.